OPTIMALISASI PEMANFAATAN ASET DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH: Studi Kasus : Badan Pengelola Keuangan dan Aset Daerah Kota Jayapura - Silaban, Henra; Fallah, Syaikul; Kristian, Ferdinandus (Universitas Cenderawasih, 2023)
ABSTRACT In these recent years (2019-2022) the Local Revenue (LR) of Jayapura City is so volatile. This research has two purposes which is (1) Analyze the local property assets utilization that contributes the Local Revenue of Jayapura City; (2) Analyze the best strategy of local property assets utilization to increase the local revenue of Jayapura City Government. This research was conducted within the scope of Jayapura City government. The sampling technique is carried out using pusposive sampling techniques. The type of research data used in this study is a type of quantitative descriptive data. The data analysis used in this research was Contribution Analysis (Minister of Internal Affairs Decree No. 690.900.327,2015) which was carried out using Microsoft Excel. SWOT analysis was used to identify the exact strategy to optimize the local property assets utilization that expected will increase the Local Revenue of Jayapura Government The results showed that: (1) the local property assets utilization that contributes Local Revenue of Jayapura City in 2019-2022 could not exceed 2%. This number was classified in “very low” criteria and much lower than regional tax that able to contributes more than 78%. (2) There are two exact strategies to optimize local property assets utilization of Jayapura City. Firstly, Weakness reduction by enhance the performance of government officer and secondly, maximize the Opportunity by improve the partnership with the third parties. Keywords: Local Revenue, local property assets utilization, Contribution Analysis, Strategy